Traffic Flow Control System for Construction Site - Muhammad, Muhammad Helmey; Mohd Zin, Rosnah (Evolution in Electrical and Electronic Engineering, 2023)
The project is a system that can control traffic congestion when there is the construction of a building near a road that involves a two-way street becoming one-way using traffic lights that can be controlled via a smartphone. This project was proposed to facilitate site-related works, it was easier to control traffic without requiring more manpower, in addition, this system also has 3 modes that allow traffic lights to operate according to traffic congestion. This project has two stages of design namely hardware and software. The hardware uses a microcontroller ESP8266 Wi-fi module and an IR sensor Module, while the software is a Blynk app that can be controlled via a smartphone. The position and orientation of the traffic flow control system can be achieved using vehicle movement through three specially created modes. The system trial was carried out in three modes, which are mode 1 representing normal traffic, mode 2 representing busier traffic, and mode 3 representing vehicles entering and exiting the construction site. All the results show that the system can work well with accuracy.